ANALISIS KONTEKS PENGELOLAAN BARANG MILIK DAERAH KABUPATEN KONAWE SELATAN - Syamsul Alam; Zulfiah Larisu (Halu Oleo University, 2023)
Context is recognized as having an influence on the efficient operation of public administration, including the management of local government assets. However, there is a lack of research exploring the topic. The purpose of this study is to analyze the context of asset management of the South Konawe Regency government. The context of asset management is analyzed from four aspects, namely needs, root problems, opportunities, and objectives of asset management. This research uses a qualitative method approach. Data were collected through semi-structured interviews. The data analysis technique used is a qualitative analysis of interactive models. The results show that there is a lack of clarity in the context of regional asset management, with differences between ideality and reality, which has the potential to harm the efficiency and achievement of long-term goals of local governments.